The STUDENTS' PERCEPTION ABOUT SONG LYRIC IN VOCABULARY LEARNING AT TENTH GRADE OF SMAN 9 PADANG - Aini, Dinda; Elda Martha Suri; Widya Juli Astria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ekasakti, 2024)
It needs appropriate and effective media to help the students learn vocabulary. This research used a descriptive method to explore students' perception thoughts toward using song lyrics as a learning media. The population of this research was tenth-grade students of SMAN 9 Padang at the academic year of 2024/2025 The research process used a cluster random sampling technique to decide the subject. The researcher got class X E2 as the sample which consists of 36 students. The researcher used questionnaire to collect the data. There are 20 statements in the questionnaire. The researcher gave the questionnaire to the students by using paper, and the duration for them to fill it was 30 minutes. The researcher used the Likert scale procedure to analyze the data. Based on the finding of the research, the researcher found that about 66.1% participants have positive perception of the use of song lyric for learning English, especially in vocabulary learning. As a result, 77% of students agreed that song lyric is effective media for vocabulary learning, 76% of students have positive perceptions about the learning outcomes, and 64% students also had positive perceptions about the experience while using song lyric as a media for vocabulary learning.